An Evaluation of Consumer Protection Legislation: The 1962 Drug Amendments - Peltzman, Sam (Journal of Political Economy, 1973)
The 1962 drug amendments seek to prevent wasted expenditure stimulated by exaggerated claims for effectiveness of new drugs by requiring premarketing approval of all new drug claims by the Food and Drug Administration. The compliance costs are shown to have engendered a marked reduction in drug innovation. Consumer surplus analysis is then adapted and supplemented with "expert" drug evaluations to estimate the relevant benefits and costs. The main finding is that benefits forgone on effective new drugs exceed greatly the waste avoided on ineffective drugs. The estimated net impact is equivalent to a 5-10 percent tax on drug purchases.